Correlation of Hop test with Speed at thirty meters test in infants between ten and twelve years of a private school in Santiago de Chile (Correlación del Single Hop Test con la prueba de Velocidad en treinta metros en infantes entre diez y doce años de - Oyarzo Mauricio, Claudio Antonio; Said Negrete, María Josefina; Nazar Araya, María Jesús (Retos, 2017)
The speed, fundamental quality in sports, is predicted with horizontal and vertical jumping test. The single hop test, functional evaluation of monopodal long jump has not been studied in this area. Objetive: Correlate hop test with the thirty meters sprint test and with two leg horizontal jump, gold standard in speed prediction. Materials and Method: A study was conducted in pediatric population (n = 91) between ten and twelve years of age from a private school in Santiago, Chile. The children were submittted to thirty meters speed test, standing long jump test and hop test with both limbs. The study variables were tested for normal distribution, correlation and linear regression. The same tests were apply per gender and in subjects without asymmetries. Results: The single hop test showed a significant moderate correlation with the time achieved in thirty meters (right r= -.55; left r= -.58) like jump feet together test (r= -.49). Between jump feet together and the single hop test there was a significant moderate correlation (r=.73). The single hop test found a 39.566% of children have one leg jump asymmetry between limbs. There wasn’t changes differentiating by gender and by discount the asymmetric subjects. Conclusions: The single hop test is correlate with the sprint in thirty meters similar to the jump feet together and could be used as tool to predict speed in subjects of ten to twelve years. It also detect functional asymmetry of the long jump in children that suggested intervene to prevent possible injury. Resumen. La velocidad, cualidad fundamental en deportes, se predice con pruebas de salto horizontal y vertical. El single hop test (SHT), evaluación funcional de salto monopodal en longitud, no ha sido estudiado en esta área. Objetivo: Correlacionar single hop test con prueba de velocidad en treinta metros y salto a pies juntos (SPJ), gold estándar en predicción de velocidad. Materiales y Método: Se realizó un estudio en población infantil (n=91) entre diez y doce años de edad de un colegio de Santiago de Chile. Los niños fueron sometidos a pruebas de velocidad a través del tiempo alcanzado en treinta metros, longitud de SPJ y en SHT con ambas extremidades. Las variables en estudio fueron sometidas a pruebas de distribución normal, de correlación y regresión lineal. Las mismas pruebas se aplicaron por sexo y en sujetos sin asimetrías. Resultados: El SHT mostró una correlación significativa moderada con tiempo alcanzado en treinta metros (derecho r= -55; izquierdo r= -.58) al igual que SPJ (r= -.49). Entre SHT y SPJ hubo una correlación significativa y moderada (r= .73). El SHT pesquisó que un 39,5% de los niños presenta asimetría entre extremidades. No hubo cambios al diferenciar por sexo y al descartar sujetos asimétricos. Conclusiones: El SHT se correlaciona con la velocidad en treinta metros al igual que SPJ y podría ser utilizado como herramienta para predecir velocidad en sujetos de diez a doce años. Además, detecta asimetría funcional del salto en longitud en niños, que se sugiere intervenir para evitar posibles lesiones.